THE POTENTIAL OF PLURIPOTENT STEM CELL-BASED THERAPY AND EXTRACELLULAR VESICLES IN PROMOTING TISSUE REGENERATION - Fitria; Muslimah; Zulnandar (Journal of Stem Cell Research and Tissue Engineering, 2024)
Stem cell research has paved the way for revolutionary regenerative therapies targeting damaged and diseased tissues. Beyond traditional cell transplantation, current evidence suggests that therapeutic benefits are primarily mediated through paracrine effects. Extracellular vesicles (EVs), which can traverse biological barriers and deliver bioactive molecules, represent a promising avenue for cell-free therapy. Tissue engineering, as the second-generation regenerative innovation, integrates biodegradable 3D scaffolds with cells to mimic natural extracellular matrices, enhancing therapeutic outcomes. This study examines the potential of EVs across diverse applications. In ocular regeneration, neural progenitor-derived EVs preserve photoreceptor cells and mitigate retinal inflammation in retinitis pigmentosa. For skin repair, EVs derived from mesenchymal stem cells (MSCs) support key phases of wound healing by modulating macrophage polarization and activating molecular pathways like RAC-alpha and Notch signaling. In cardiovascular therapy, EVs contribute to heart tissue recovery, reduce myocardial apoptosis, and combat fibrosis through targeted gene modulation. Skeletal muscle regeneration benefits from EVs enhancing myogenic differentiation, decreasing fibrosis, and addressing excessive extracellular matrix accumulation common in disorders like muscular dystrophy. The ability of EVs to emulate paracrine signaling processes expands the horizons of regenerative medicine, offering a scalable and efficient alternative to cell-based therapies. Literature highlights the critical role of high-quality, large-scale production under stringent standards to ensure therapeutic consistency. These findings underscore EVs as potent, cell-free agents capable of driving tissue repair and regeneration. Further investigations are encouraged to optimize production, application, and integration with advanced biomaterials for clinical efficacy.